Therapeutical administration of peptide Pep19-2.5 and ibuprofen reduces inflammation and prevents lethal sepsis - Heinbockel, Lena; Mier, Walter (PLOS ONE, 2015)
Sepsis is still a major cause of death and many efforts have been made to improve the physical condition of sepsis patients and to reduce the high mortality rate associated with this disease. While achievements were implemented in the intensive care treatment, all attempts within the field of novel therapeutics have failed. As a consequence new medications and improved patient stratification as well as a thoughtful management of the support therapies are urgently needed. In this study, we investigated the simultaneous administration of ibuprofen as a commonly used nonsteroidal anti-inflammatory drug (NSAID) and Pep19-2.5 (Aspidasept), a newly developed antimicrobial peptide. Here, we show a synergistic therapeutic effect of combined Pep19-2.5-ibuprofen treatment in an endotoxemia mouse model of sepsis. In vivo protection correlates with a reduction in plasma levels of both tumor necrosis factor α and prostaglandin E, as a likely consequence of Pep19-2.5 and ibuprofen-dependent blockade of TLR4 and COX pro-inflammatory cascades, respectively. This finding is further characterised and confirmed in a transcriptome analysis of LPS-stimulated human monocytes. The transcriptome analyses showed that Pep19-2.5 and ibuprofen exerted a synergistic global effect both on the number of regulated genes as well as on associated gene ontology and pathway expression. Overall, ibuprofen potentiated the anti-inflammatory activity of Pep19-2.5 both in vivo and in vitro, suggesting that NSAIDs could be useful to supplement future anti-sepsis therapies.
Gesehen am 23.02.2017